Pengaruh Kemudahan Pembayaran Menggunakan QRIS, Komunikasi Pemasaran, Digital Marketing Terhadap Keputusan Pembelian - Erliyani, Ita (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study was conducted to determine the effect of ease of payment using QRIS, marketing communication, and digital marketing on purchasing decisions. The type of research used is quantitative. The sample method is nonprobability sampling with purposive sampling, analyzing data using IBM SPSS Statistics 26. The sample used and met the research criteria was 100 people. The data collection method used a questionnaire with a Likert scale. The data analysis technique used in this study was multiple linear regression. The results of the analysis show that ease of payment using QRIS has a positive and significant effect on purchasing decisions. Marketing communication has a positive and significant effect on purchasing decisions. Digital marketing has a negative, significant effect on purchasing decisions. The results of this study obtained an Adjusted R Square value of 69.8%. The results of simultaneous research on ease of payment using QRIS, marketing communication, and digital marketing have a positive and significant effect on purchasing decisions for ShopeePay users in Tangerang City.